Scope of Bachelor of Computer Application (BCA) program - Pant, Lalit (DMC Research Journal, 2018)
The main focus of this study is to posit many opportunities on IT sector and it aims to direct students in building their self-confidence to work on various fields of IT sector such as software companies, IT offices, Media print houses, school/college etc. Students will be able to identify, evaluate & solve the technical issues and get knowledge on various tools and techniques of software development. In the same vein, students will be owner of their own company and will be capable to create job opportunities for others.